Impact of different parameters on the outcome of vv-ECMO therapy in burn patients – a retrospective cohort study from a burn and high output ECMO center - Bingoel Alperen S.; Schlottmann Frederik; Plinke Clarissa; Dastagir Khaled; Obed Doha; Enechukwu Anieto; Dieck Thorben; Wellkamp Lukas; Hanke Jasmin Sarah; Kühn Christian; Ruhparwar Arjang; Krezdorn Nicco; et al. (Innovative Surgical Sciences)
The treatment of acute respiratory distress syndrome (ARDS) in burn patients remains a major challenge. Veno-venous extracorporeal membrane oxygenation (vv-ECMO) is a standard treatment for severe ARDS today. But reports on survival outcome in burn patients remain variable in the literature. The aim of this study is to identify factors that may influence survival and therapy outcomes in this distinct patient population.